The determining of the force for corn-cobs separation - V. Hruban; V. Havrysh; А. Kalinichenko (Вісник аграрної науки Причорномор'я, 2021)
There has been an increase in demand of corn in the world. This requires the use of high-performance agricultural machinery, including combine harvesters. However, corn harvesters have high grain losses and their apparatuses must be improved. The aim of the article was justification of corn picker operation by developing a mathematical model of the process of cobs separation in the complex combination several forces. To verify this model the results of the simulation were compared to experimental data. The wave theory has proved to be more accurate compared to the static model. The results of the theoretical researches of the methods of corn-cobs separation from stems are given and mathematical models are worked out. The technological process of corn-cobs separation fulfilled by the combination of different forces and the valuation of the resulting tension. The technological process of cobs separation is considered in combination of many forces, and making assessments of the resultant tension. Further research will be focused on the intensification of this process by the integration of stretching the stalk together with its twisting